Gypsum-plasters mixed with polystyrene balls for building insulation: Experimental characterization and energy performance. (10th May 2021) - Bouzit, S.; Merli, F.; Sonebi, M.; Buratti, C.; Taha, M.
Highlights: Composites made of Moroccan natural gypsum plasters with polystyrene balls are studied. Influence of balls characteristics on mechanical, thermal, and acoustic performance is investigated. The plaster with 10 wt% of 3-mm balls increases the thermal performance up to 27%. Sound insulation and mechanical properties are slightly reduced with 10 wt% of 3-mm balls. Energy demand reduction up to 16% is obtained with 30% polystyrene content. Abstract: In order to reduce the heat loss from envelopes and to ensure energy saving in building refurbishment, polystyrene balls are added to Moroccan natural gypsum plaster. A complete characterization of the mechanical, thermal, and acoustic properties of the samples is carried out, taking into account different contents and diameters of the polystyrene balls. Increasing balls size, flexural strength peak value occurred with a lower polystyrene percentage. Thermal properties were measured by means of Small Hot Box apparatus. The values of conductivity were 0.191 and 0.116 W/mK for 10% and 30% addition of the smallest polystyrene balls, respectively. The acoustic properties were measured by means of a Kundt's Tube, in terms of absorption coefficient and sound insulation. The absorption coefficients were slightly higher than the ones of standard plasters. As concerning insulation properties, a worse performance was expected, due to the lower density of the samples with the balls, according to the Mass Low. Anyway the transmission loss values were up to 45 dB, with a reduction of only 2–3 dB with respect to the samples without balls, showing a good performance for the proposed composites. Finally, dynamic energy simulations for a case study showed that polystyrene plaster with smaller balls applied on the wall surfaces of a residential building involved benefits both for heating and cooling energy demand. A small thickness (3 cm) of insulating material could be a suitable solution in order to enhance the thermal and acoustic performance and to reduce environmental impact of the construction systems.